Tuning the Hall conductivity with rotation. (29th April 2015) - Filgueiras, C.; Brandão, J.; Moraes, F.
Abstract: In this work we investigate the effects of rotation in the integer quantum Hall effect. We verify that the quantization of the Hall conductivity comes from the quantization of a generalized gauge field flux as predicted by Fischer and Schopohl ( Europhys. Lett., 54 (2001) 502) and show that rotation can be used to fine-tune the conductivity plateaus.